2021
DOI: 10.3390/ma14071719
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Dielectric Properties of Ecoflex® with L,D-Poly(Lactic Acid) or Polycaprolactone in the Presence of SWCN or 5CB

Abstract: The main goal of this paper was to study the dielectric properties of hybrid binary and ternary composites based on biodegradable polymer Ecoflex®, single walled carbon nanotubes (SWCN), and liquid crystalline 4′-pentyl-4-biphenylcarbonitrile (5CB) compound. The obtained results were compared with other created analogically to Ecoflex®, hybrid layers based on biodegradable polymers such as L,D-polylactide (L,D-PLA) and polycaprolactone (PCL). Frequency domain dielectric spectroscopy (FDDS) results were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
0
12
0
2
Order By: Relevance
“…6, the FTIR, XRD, DSC and TGA analyses were performed to thoroughly harness the crystal structure and thermal properties of all PVDF-based composite films with different content of 5CB. With increasing 5CB content, the absorption band at 2226 cm −1 of the C≡N group of 5CB is observed, and the characteristic peaks at 1606 cm −1 and 1494 cm −1 are a result of phenyl C–C stretching of 5CB, 42,43 as shown in Fig. 6(b).…”
Section: Resultsmentioning
confidence: 89%
“…6, the FTIR, XRD, DSC and TGA analyses were performed to thoroughly harness the crystal structure and thermal properties of all PVDF-based composite films with different content of 5CB. With increasing 5CB content, the absorption band at 2226 cm −1 of the C≡N group of 5CB is observed, and the characteristic peaks at 1606 cm −1 and 1494 cm −1 are a result of phenyl C–C stretching of 5CB, 42,43 as shown in Fig. 6(b).…”
Section: Resultsmentioning
confidence: 89%
“…Carbon nanomaterials such as carbon nanotubes improved the dielectric properties of commercially available polymers, Ecoflex ® [187]. It was found that there is an increase in the dielectric value with the rise of the carbon nanotube's contents.…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…Carbon nanomaterials such as carbon nanotubes improved the dielectric properties of commercially available polymers, Ecoflex ® [130]. It was found that there is an increase in the dielectric value with the rise of the carbon nanotube's contents.…”
Section: Good Toughnessmentioning
confidence: 99%